Multiple buffer CoCos and their impact on financial stability - Ioana Neamtu (Tinbergen Institute, 2020)
In this paper we develop a theoretical model to investigate the effect on a bank's financial stability of having multiple contingent convertible bonds buffers (CoCos) on the same bank balance sheet, using cash-in-the-market pricing and global games methodologies. Contingent convertible bonds are meant to act as a bail-in mechanism for banks, where CoCo debt converts into equity when a bank needs it the most. We find that having CoCo buffers which trigger at different capitalisation levels can be detrimental for the CoCo bail-in capacity. Market-based triggers lead to premature conversion and fire-sales of equity. In contrast with existing literature, we show that book-based trigger CoCos yield an optimal outcome, as long as they incorporate expected credit losses.
Keywords: G38; G21; G32; 330; contingent convertible bonds; fire sales; financial stability